Interfacial Effects on the Growth of Atomically Thin Film: Group VA Elements on Au(111). Issue 21 (9th September 2019) - Zhou, Dechun; Si, Nan; Jiang, Bohong; Song, Xiufeng; Huang, Han; Ji, Qingmin; Niu, Tianchao
Abstract: The understanding of growth mechanism at atomic scale is a key issue for realizing wafer‐scale, high‐quality 2D materials, in which their interfaces play a crucial role. Here, the adsorption and the aggregation of group VA elements within the first layer on Au(111) are investigated. Together with recent results for group VA elements on Cu and Ag(111), this study leads to a comprehensive understanding of the interfacial effects on the surface structures. Blue phosphorene forms the typical (4 × 4) honeycomb structure on Au(111) regardless of the coverage. Sb assembles into multiple intermediate phases comprising dimer pairs and coin‐shaped aggregates depending critically on the coverage. Increasing the coverage and annealing temperature converts these dimer pairs to AuSb2 surface alloy. The ( 37   ×   37 ) honeycomb structure and ( 5   ×   3 ) periodic stripes are the most stable of Bi on Au(111). Notably, neither P nor Bi prefers surface alloy under the similar growth conditions even though they have the smaller and larger atomic radius, higher and lower electronegativity than Sb, respectively. This difference is correlated with the relativistic effect that tightly bound inner 6s 2 electrons make Bi inert. These model systems provide guidance framework for selection of elements and substrates to synthesize monoelemental and binary 2D materials. Abstract : Substrate, stability, and synthesis are the key factors that determine the applications of elemental two‐dimensional materials. Using group VA elements on Au(111) as model systems, the interfacial effects on the adsorption and aggregation are systematically investigated. Besides the lattice match, strength of interfacial interaction determines the formation of phosphorene, AuSb2 alloy and Bi atomic layer on Au(111).